ANALISIS WACANA KRITIS PADA IKLAN LAYANAN PENDIDIKAN KAJIAN NORMAN FAIRCLOUGH - Arpiana Anwar; Syahruddin; Rosmini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Critical Discourse Analysis in Educational Service Advertisements Study by Norman Fairclough. Thesis. This research aims to describe the linguistic features of critical discourse analysis in Educational Service Advertisements. This research uses a qualitative descriptive method. The qualitative descriptive method is research that produces data in the form of words or verbally. The focus of this research is critical discourse analysis at the level of analysis of educational service advertising texts which are studied using the Norman Fairclough model. The data in this research is written discourse in Educational Service Advertisements. The data collection techniques used are observation and note taking/recording. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The research results show that there are forms of AWK linguistic features in Educational Service Advertisements. The linguistic features are lexical processes, meaning relations, metaphors, euphemistic expressions, formal and informal words, positive and negative evaluation, nominalization, passification, use of positive and affirmative sentence forms, sentence modes, modality, text ordering, and control. participants. From data 1 to data 16 what was found were the linguistic features of lexical processes, meaning relations, positive sentence forms and participant affirmation and control.